Combustion of ethanol+air mixture supported by transverse arc plasma - Yukhymenko, V.V.; Chernyak, V.Ya.; Naumov, V.V.; Veremii, Iu.P.; Zrazhevskij, V.A. (Вопросы атомной науки и техники, 2007)
The influence of preliminary plasma reforming of fuel on plasma combustion efficiency was investigated. The ethanol was chosen as researched fuel. The electrical discharge in the gas channel with a liquid wall was used for preliminary ethanol reforming. The burning was supported by transverse arc discharge in a flow of mix air + reformed ethanol. Emission spectroscopy of plasma was applied to control of burning process. Offered a plasma method for testing of burning efficiency of fuel.